2015
DOI: 10.1111/1365-2745.12372
|View full text |Cite
|
Sign up to set email alerts
|

Environmental heterogeneity leads to higher plasticity in dry‐edge populations of a semi‐arid Chilean shrub: insights into climate change responses

Abstract: Summary 1.Interannual variability in climatic conditions should be taken into account in climate change studies in semiarid ecosystems. It may determine differentiation in phenotypic plasticity among populations, with populations experiencing higher environmental heterogeneity showing higher levels of plasticity.2. The ability of populations to evolve key functional traits and plasticity may determine the survival of plant populations under the drier and more variable climate expected for semi-arid ecosystems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
104
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 95 publications
(121 reference statements)
13
104
0
1
Order By: Relevance
“…Moreover, SWA shows a stronger difference between dry and wet periods, has clearer unimodal shapes along the MAP gradient and possesses higher variability along the MAP gradient. This agrees with the hypothesized higher β dynamics in regions with higher interannual variability of annual rainfall [36,37], such as SWA (Figure 3a). In addition, this suggests that a higher rain use efficiency, which has been observed during dry periods [18], might be particularly favoured by greater rainfall variability.…”
Section: Vegetation Response To Rainfall Along Map Gradientssupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, SWA shows a stronger difference between dry and wet periods, has clearer unimodal shapes along the MAP gradient and possesses higher variability along the MAP gradient. This agrees with the hypothesized higher β dynamics in regions with higher interannual variability of annual rainfall [36,37], such as SWA (Figure 3a). In addition, this suggests that a higher rain use efficiency, which has been observed during dry periods [18], might be particularly favoured by greater rainfall variability.…”
Section: Vegetation Response To Rainfall Along Map Gradientssupporting
confidence: 89%
“…Both can be expected from the overall higher β in SWA (Figure 4a). It thus further supports the hypothesis that greater rainfall variability (CVP, Figure 3a) may lead to a temporally more dynamic vegetation response to rainfall [37,67]. MAP β-max values (the positions of β max on the rainfall gradients) are significantly lower in SWA compared to WA (Figure 4c).…”
Section: Dynamics Of Peak Vegetation Response To Rainfallsupporting
confidence: 76%
See 2 more Smart Citations
“…Lázaro-Nogal et al (2015) found greater phenotypic plasticity being associated with higher rainfall variability in dryland plant communities which is considered an important feature for dryland ecosystems in face of future changes in rainfall. Thus, it may be hypothesized that higher rainfall variability promotes a more dynamic vegetation functional response to rainfall.…”
mentioning
confidence: 88%